Хозяин янтаря: [фантастический роман] / Александр Шакилов - Шакилов Александр (S.T.A.L.K.E.R., 2010)
Экземпляры: ф.18 (20200615) / Инвентарный номер: 3440 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ш 12 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445